ANALISIS DIFUSI KERUANGAN DI SEKITAR KAWASAN PERKOTAAN YOGYAKARTA - Nurul Faizah, Arina; Hendarto, Mulyo (Diponegoro Journal of Economics, 2013)
The rapid population growth in cities will lead to the increasing of the growth size of urban areas therefore it will generate the urban aglomeration afterwards.Â  The urban areas tends to expand to the periphery area because of the lack of land supply in cities. The urban size of Yogyakarta has experienced increased significantly. In this moment, the urban area of Yogyakarta has reached until Sleman regency and partly of Bantul regency. This study identify the phisical, social, economic transformation and also the spatial diffusion effect that has already occurred in urban area of Yogyakarta.This study shows that the forming of urban area of Yogyakarta and surrounding gives impacts of phisical transformation such as the increasing of built area which generate the land prices rise and the infrastructure and social facility adequate in the periphery. The activity in city lead as the generator of the spatial diffusion to the periphery and also economic of scale which is the increase in efficiency of production as the number of goods being produced increases.